A small molecule that disrupts S. Typhimurium membrane voltage without cell lysis reduces bacterial colonization of mice - Dombach, Jamie L.; Quintana, Joaquin LJ; Allgood, Samual C.; Nagy, Toni A.; Gustafson, Daniel L.; Detweiler, Corrella S. (PLOS Pathogens, 2022)
As pathogenic bacteria become increasingly resistant to antibiotics, antimicrobials with mechanisms of action distinct from current clinical antibiotics are needed. Gram-negative bacteria pose a particular problem because they defend themselves against chemicals with a minimally permeable outer membrane and with efflux pumps. During infection, innate immune defense molecules increase bacterial vulnerability to chemicals by permeabilizing the outer membrane and occupying efflux pumps. Therefore, screens for compounds that reduce bacterial colonization of mammalian cells have the potential to reveal unexplored therapeutic avenues. Here we describe a new small molecule, D66, that prevents the survival of a human Gram-negative pathogen in macrophages. D66 inhibits bacterial growth under conditions wherein the bacterial outer membrane or efflux pumps are compromised, but not in standard microbiological media. The compound disrupts voltage across the bacterial inner membrane at concentrations that do not permeabilize the inner membrane or lyse cells. Selection for bacterial clones resistant to D66 activity suggested that outer membrane integrity and efflux are the two major bacterial defense mechanisms against this compound. Treatment of mammalian cells with D66 does not permeabilize the mammalian cell membrane but does cause stress, as revealed by hyperpolarization of mitochondrial membranes. Nevertheless, the compound is tolerated in mice and reduces bacterial tissue load. These data suggest that the inner membrane could be a viable target for anti-Gram-negative antimicrobials, and that disruption of bacterial membrane voltage without lysis is sufficient to enable clearance from the host.